Caracterización de actinomicetos rizosféricos con potencial benéfico en semillas de maíz (Zea mays - Miquinga Tucres, Ana María (2022)
Actinomycetes that colonize the rhizosphere of plants are important in promoting plant growth through the production of biologically active substances. The objective of this study was to characterize actinomycetes from the rhizosphere, evaluate their biostimulant capacity as a plant growth promoter in maize in vitro, and their potential to control phytopathogens.